Food Waste Management Hotel Restaurant in Pontianak City - Erval Alziansyah; Maswadi Maswadi; Wanti Fitrianti (International Journal Labs, 2025)
This study aims to analyze food waste management in star hotels in Pontianak City with a case study of Aston Pontianak Hotel Restaurant, as well as formulate alternative reduction efforts. The background of the research is the high generation of food waste in Indonesia and the absence of a special policy on food loss and waste, while hotels are one of the significant producers of food waste. The research was conducted in September-November 2023 with a qualitative descriptive approach using purposive sampling techniques on chefs, waitresses, and breakfast visitors, and supported by secondary data. Data was collected through observation, interviews, and questionnaires, then analyzed descriptively. The results showed that food waste appeared most at the receiving, storage, and production stages in the Operating Control Cycle, and the amount of generation was greatly influenced by the number of visitors and consumer behavior during the buffet (food taste was not suitable and the portion was excessive). Respondents assessed reducing the size of cutlery and consumer education as the most preferred method to reduce food waste. This study recommends improving menu management, strengthening kitchen training, and establishing a more sustainable food waste treatment system.